THE IMPACT OF TRADE LIBERALIZATION ON POVERTY REDUCTION IN INDONESIA - Adha, Mufti Alam; Nahar, Faiza Husnayeni; Azizurrohman, Muhammad (Jurnal Ekonomi & Studi Pembangunan, 2018)
Nowadays, trade liberalization is considered as development strategy policy to increase economic growth and reduce poverty in many countries, particularly in developing countries. It is reported that Indonesia has been actively joining many trade agreements in order to ease the distribution of goods and services to other countries. Hence, this study analyses the impact of trade liberalization on poverty reduction by using an Ordinary Least Square (OLS) method from 1984 to 2017. The Trade Openness Ratio (TOR) is used as a dependent variable in order to measure trade liberalization. Other variables such as GDP, exchange rate and labor force are considered as control variables. The empirical result shows that TOR and labor force have a positive impact on poverty, whereas GDP and exchange rate have a negative impact. This finding is different with previous researches, particularly where trade liberalization has been negatively affecting poverty. Such a result is justifiable because Indonesian firms are not ready to compete with foreign firms where high competitiveness exist.Â